Problematika Pengisian Jabatan Menteri Yang Membidangi Birokrasi di Indonesia - Sorik, Sultan; Natalia, Siska Windu; Yustiyah, Erma; Dwiatmoko, Anang (UI Scholars Hub, 2022)
This study examines the problems of filling ministerial positions in charge of the bureaucracy in Indonesia. The form of research used is normative juridical. From the research conducted, it was found that, 1) in the midst of the spirit of the State Civil Apparatus Law to implement the Merit System in human resource management, one of the important things that was forgotten was about filling in the ministerial positions in charge of bureaucracy, which is the spearhead of bureaucratic policy makers in Indonesia. Indonesia; 2) pressure from political parties was very influential in selecting ministers in the cabinet during the period of President Jokowi's administration, so it is not surprising that ministers in charge of bureaucracy are often from political parties; 3) filling the position of minister in charge of the bureaucracy in Indonesia contradicts the theory put forward by Max Weber. If the assistant to the president (minister) still comes from a political party, there will be problems of loyalty, a minister will find it difficult to get out of the double loyalty trap, between serving the president or the head of a political party. So that in the future filling ministerial positions, especially those in charge of bureaucracy, indicators need to be made, so that the minister can help carry out his duties in the implementation of a better state government and not be trapped in double service between the president and the chairman of political parties.